Evaluation of complications of laparoscopic cholecystectomy in a single centre experience - Sikder, AH; Hasan, F; Zaman, S; Amin, R (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Laparoscopic cholecystectomy first introduced by Muhe in 1985 followed by Muret in1987, it is becoming more popular and now it is gold standard for symtomatic gallstone disease. Objective: To determine the complication of Laparoscopic cholecystectomy in our series. Materials and Methods: A total 150 patients with gallstone disease whose wall thickness of gallbladder were 3mm were selected for Laparoscopic cholecystectomy, Acute cholecystitis, choledocholithiasis, obstructive jaundice, Gallbladder mass or dilated CBD, were excluded. Details histroy, physical examination, and relevant investigation were done (including LFT, HbsAg, Anti HCV) and patients were checked for anesthesia fitness, then laparoscopic cholecystectomy were done, operative finding and outcome observed. Results: Among 150 patients there were 126patients were female and 24 patients were Male, age ranges from 16 to 65 yrs. Laparoscopic cholecystectomy were done successfully in 140 patients (92%) and conversion done in teen patients(6.6%). Major complications were seen in five (3.3%) patients, including common bile duct (CBD) injury in two patients, duodenal injury in one patient, bleeding from gall bladder bed in two patients. There was no mortality in the study. Conclusion: Laparoscopic cholecystectomy is a safe and effective treatment for gallstone disease. J. Dhaka National Med. Coll. Hos. 2019; 25 (02): 22-24